A thousand words about cardiac mobile health - Noori, Vincent; Guzik, Przemysław (Journal of Medical Science, 2014)
Cardiac mHealth (mobile health) is an innovative method of integrating technological and medical advances to provide healthcare in a convenient and cost effective manner in cardiology. While still considered an experimental and upcoming technology, its potential use in cardiology is feasible and may soon replace some standard medical practices. From basic encouragement of lifestyle modification to chronic disease self-management, mHealth can be a personal “pocket-doc”. It can provide personal health benefits and immediate life-saving interventions to those who are unable to access medical care. mHealth’s potential has much to offer to both physicians and patients.